MEMUTUS OLIGARKI DAN KLIENTELISME DALAM SISTEM POLITIK INDONESIA MELALUI PEMBAHARUAN PENGATURAN PENDANAAN PARTAI POLITIK OLEH NEGARA - Syawawi, Reza (Jurnal Legislasi Indonesia, 2021)
The objective of State funding for political parties is to create balance in governing political parties. The minimum intervention from the state to political parties will cause political parties controlled by the oligarchs. These oligarchs have the intention in the making of policies or regulations. The domination of elites in funding the political parties create clientelism in the electoral processes. In this context, increasing the state funding for political parties can be chosen as a recommendation. But it should be followed by the accountability in reporting the finance and improvement of political parties governance. This recommendation should be applied the revision in the law of political parties. The existing law of political parties are not maximally regulate about the accountability of political parties. The obligations, restrictions, and sanctions that are stated in the law are unable to cut the illegal funding for political parties. The design of oversight in political party finance are seems to unable control the illegal funding such as funding from individual donors or private sector. According to that, it is important to increase the state funding for political party along with increasing the accountability of the political party finance and improving the political party governance.